The Regulation of Wakaf Tunai Calon Pengantin as a Cash Waqf Scheme for Advancing Mashlahah for Family Economic Resilience - Hanifa Aini; Yasniwati; Devianty Fitri (Journal of Law, Politic and Humanities, 2026)
This research examines the legal status of Cash Waqf for Prospective Brides and Grooms (WTC) in islamic regulatory frameworks to ensure legal certainty and enhance transparency. This research is a descriptive normative juridical research with statute approach and conceptual approach. The results of this research indicate that the normative status of WTC remains unclear, leading to legal uncertainty and gaps that need to be addressed immediately. Substantively, WTC aligns with maqashid syariah as it is oriented towards strengthening family economic resilience. However, in practice, it has not been realised due to unclear guidelines for implementation, low wakaf literacy, a lack of transparency, conflicts with extortionate fees, and the failure to distribute benefits effectively. This research recommends that WTC need to be supported by technical regulations aligned with national waqf law, involving BWI and the Ministry of Religious Affairs and that the concept of mashlahah mursalah serve as the foundation for drafting family-oriented regulations, such as BWI decrees, circular letters, and operational guidelines for the WTC. The optimalisation of the role of the BWI, the Ministry of Religious Affairs, and the BWI representatives, and strengthening of transparency through a real-time dashboard similar to the 'SatuWakaf' system.